2021
DOI: 10.1042/bsr20210979
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, a major risk factor for immunity and severe outcomes of COVID-19

Abstract: An influenza-like virus named SARS-CoV-2 is responsible for COVID-19 disease and spread worldwide within a short time. COVID-19 has now become a significant concern for public health. Obesity is highly prevalent worldwide and is considered a risk factor for impairing the adaptive immune system. Although diabetes, hypertension, cardiovascular disease, and renal failure are considered the risk factors for COVID-19, obesity is not yet well-considered. This study approaches establishing a systemic association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 167 publications
1
13
0
Order By: Relevance
“…Our study is further closely located to a previous report that indicated increased risks of acquiring COVID-19 infection among pediatrics with medical comorbidities and certain disorders such as obesity [57]. Obesity should be recruited as individual risk factors for higher COVID-19 severity and mortality outcomes [58]. Obesity is a well-known risk factor for acquiring COVID-19 and infections in general [59].…”
Section: Discussionsupporting
confidence: 70%
“…Our study is further closely located to a previous report that indicated increased risks of acquiring COVID-19 infection among pediatrics with medical comorbidities and certain disorders such as obesity [57]. Obesity should be recruited as individual risk factors for higher COVID-19 severity and mortality outcomes [58]. Obesity is a well-known risk factor for acquiring COVID-19 and infections in general [59].…”
Section: Discussionsupporting
confidence: 70%
“…Our findings are consistent with those of previous research on the effect of obesity on immunological fitness, which demonstrated a correlation between weight and ISQ scores. Obesity is a distinct risk factor [ 33 ]. Obesity has recently been associated with higher mortality and disease severity during the COVID-19 pandemic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18] According to research statistics, the prevalence rate of obesity and abdominal obesity in China is 13.2% and 44%, respectively, indicating that the number of patients should not be underestimated. [19] Obesity is an independent risk factor for the onset of influenza. Generally, obese people with a BMI of 30-35 kg/m 2 and more than 35 kg/m 2 have 1.45 and 2.12 times, respectively, the risk of being hospitalizationed for influenza.…”
Section: Obesity and Morbidity Of Covid-19mentioning
confidence: 99%
“…[ 18 ] According to research statistics, the prevalence rate of obesity and abdominal obesity in China is 13.2% and 44%, respectively, indicating that the number of patients should not be underestimated. [ 19 ]…”
Section: Obesity and Morbidity Of Covid-19mentioning
confidence: 99%